Language Difficulties and Challenges Faced by Students in Understanding the English Curriculum at PNS LUMHS: Difficulties and Challenges in Understanding English Curriculum - Iqra, .; Channar, Husan Bano; Khowaja, Shehneela; Bhacho, Abdul Hameed; Dean, Rubina; Haq, Mansoor Ul (Pakistan BioMedical Journal, 2025)
The English language is spoken all over the world nowadays. It is issued in various socio-economic settings such as tourism, travelling, business, commerce, communication, teaching, learning, international diplomacy, science and technology. Objectives: To describe the challenges that students experience because of the curriculum in English. To investigate how these challenges are overcome by students in their academic years, and to explore which strategies are used by students to overcome challenges faced because of the curriculum in English. Methods: A cross-sectional study was carried out at Peoples Nursing School, Liaquat University of Medical and Health Science, Jamshoro, to evaluate language difficulties and challenges faced by students in understanding the English curriculum at Peoples Nursing School, Liaquat University of Medical and Health Science. Results: According to this study, nearly 41% of students face difficulties when communicating in English. 41% of students have difficulty in grammar. The major problem faced by participants is that 57% of students feel shy, and because of that students don’t communicate well in English. 53% of participants don’t speak English or read in English because of shyness and 51% of participants haven’t enough confidence to read in English in front of people. Conclusions: It was concluded that participants have major problems in English speaking because of again lack of confidence, shyness, lack of vocabulary, lack of fluency, and sentence-making problems.